Non-surgical Management of Invasive Cervical Resorption: A Case Report - TRIPATHI, DR.SHUBHAM; PATNI, DR. PALLAV; JAIN, DR. PRADEEP; RAGHUWANSHI, DR. SWADHIN; PANDEY, DR. SANKET HANS; JAIN, DR. SWATI; SONI, DR. ANKITA (Journal of Case Reports in Dental Medicine, 2023)
Objective: This article proposes a case report of Invasive cervical resorption (ICR) and its management. The prominent features were a substantial cervical resorptive defect with localized fibrous in-growth located on the cervicolabial aspect of the maxillary canine involving the enamel and dentin and pulp.Methods: A 25-year-old, male patient came to the Department of Conservative Dentistry and Endodontics with the chief complaint of bleeding gums, mild pain and small cavitation in maxillary right front tooth region since few months. The clinical diagnosis was asymptomatic irreversible pulpitis with class 3 ICR.Results: Root canal treatment with non-surgical debridement, obturation using single cone technique and restoration of the resorptive lacuna using Glass ionomer cement was done. Long term recall showed satisfactory gingival healing. Eighteen -month follow-up of the cased not reveal any recurrenceConclusion: ICR can be arrested using the "Heithersay approach" (i.e., mechanical debridement, treatment with TCA, and reconstitution).Â